Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan Pada PT. Sarana Industama Perkasa - Emma Novirsari; Nasib Nasib; Muhammad Salim Muda Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2022)
The formulation of the problem in this research is whether compensation and work environment influence employee job satisfaction. The aim of the research is to determine the effect of compensation and work environment on employee job satisfaction at PT. The research population is employees of PT. Sarana Industama Perkasa has 679 employees and the determination technique uses accidental sampling. The sample in this study amounted to 87 respondents. The data sources in this research are primary data and secondary data. Secondary data can come from data that has been documented. The data analysis techniques used are descriptive analysis and multiple linear regression. The results of the multilevel regression analysis are Y = 7.831 + 0.323X1 + 0.408X2 + e which shows that compensation and the work environment have a positive and significant effect on job satisfaction. The results of the test (t) or partial test show that compensation has a positive and significant effect on job satisfaction where it can be seen that the calculated t value is 3.928 > t table 1.989 and work environment variables also have a positive and significant effect on job satisfaction where it can be seen that the calculated t value is 4.764 > t table 1,989. So 71.6% of the variation in the dependent variable, namely compensation and work environment in the model, can explain the variable job satisfaction at PT. Sarana Industama Perkasa while the remaining 28.4% is influenced by other variables outside the model.